2008
DOI: 10.1504/ijmmm.2008.023717
|View full text |Cite
|
Sign up to set email alerts
|

Milling induced residual stresses in structural parts out of forged aluminium alloys

Abstract: Machining operations of aluminum structural parts are typically carried out under high feeds and high cutting speeds. These cutting conditions exert thermal and mechanical loads on the workpiece, which cause changes in the subsurface material. Residual stresses belong to the machining induced changes and can lead to considerable rejection rates as a consequence of part distortion. Due to the significant economic importance, it is essential to investigate the influence of the machining process on the residual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…According to residual stresses obtained results, for flank milling technique it was appreciated a tensile residual stress near to machined surface common for this technique [ 46 ]. On the contrary, flank SAM measurements showed a compressive pattern residual stress near to the manufactured surface.…”
Section: Resultsmentioning
confidence: 99%
“…According to residual stresses obtained results, for flank milling technique it was appreciated a tensile residual stress near to machined surface common for this technique [ 46 ]. On the contrary, flank SAM measurements showed a compressive pattern residual stress near to the manufactured surface.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the contact zone, the model concept includes the measuring stand components having a bearing on the accuracy and quality of identifying deformations. The full 3D model reproduces the components of the test stand developed by the authors and described in [15,16]. The following are modelled: a table, a milled rectangular specimen (made of 5083 aluminium alloy) whose top surface roughness is known, a steel punch ending in a short quadratic prism (ground and polished, with a 1 mm  1 mm square cross section), and a contact zone together with a subsurface zone, constituting the principal part of the model (Fig.…”
Section: D Model Conceptmentioning
confidence: 99%
“…Such changes can be due to specimen surface hardening and permanent deformations during machining as well as during the first loading of the specimen. In the literature on the subject [16,17] it is reported that in the case of aluminium alloy milling the residual stresses accompanying this strain hardening can reach deep into the material (as deep as 100-300 μm).…”
Section: Impact Of Subsurface Zone Materials Properties On Contactmentioning
confidence: 99%
“…It noteworthy that, in this case, the study of the residual stress left in the machined surface was limited to the tangential stress component in the cutting direction. Recently, Denkena and De Leon [14] studied the influence of cutting parameters and tool geometry on the level of residual stresses induced by milling in workpieces of forged aluminium alloys. More recently, Díaz et al [15,16] and Mammana et.…”
Section: Related Workmentioning
confidence: 99%